Characterization of cyclic plasticity type wear mechanism for titanium alloy, TI-6AL-4V on reciprocating sliding wear test - Mohd Harun, Dalila (2020)
This study presents the characterization of cyclic plasticity type wear mechanism on reciprocating sliding wear test for Titanium alloy, Ti-6Al-4V. The reciprocating sliding wear test set up by pin-on-flat configuration made from Ti-6Al-4V. Dimension of flat bar used Contact material is 100 x 25 x 8 mm. Meanwhile for the contact pin, two different diameter cylinders are used i.e Ø6.5 mm and Ø12 mm. The effects of variable parameter set up which are applied normal load (50–200 N), number of cycles (5–20 cycles), and frequency (1– 2.5 Hz) on reciprocating sliding wear behavior are investigated. Frictional force resulted 60 – 80 N tangential force in range for those three parameter setup by both two contact pins cylinder. The COF resulted running-in condition at the earlier second and highest peak experienced in value range of 0.45-0.48. The COF graph pattern shows increasing at 1 second and the decreasing continuously. For the micrography, it shows sticking mostly at the end of wear track and significant at 200 N, 20 cycles and 1 Hz frequency for those two contact pins cylinder. The profilometry shows the result of wear width and wear area where the wear width and wear area increasing with the increasing of number of cycles, applied normal load and sliding frequency for both contact pins cylinder. The hardness shows high value at 200 N, 20 cycle and 2.5 Hz of frequency. Contact pin Ø6.5 mm experienced greater wear width, wear area and hardness due to high contact pressure applied during the sliding. The cyclic plasticity presences following reciprocating sliding wear test of Ti-6Al-4V are examined using SEM. The black spot presence at the end of wear track are identified as an accumulation of ploughing that occurred during the sliding and proved by the highest hardness value recorded, 962 HV for contact pin Ø6.5 mm that determined by using Micro Vickers Hardness Tester. This is strong evidence that shows that plastic deformation is form during the sliding wear. The existing of element O by EDX analysis also proved the formation of plastic deformation. The optimum parameters to achieved high plasticity type wear behaviour also are determined. High frequency experienced low number of COF and marginal plastic deformation form during the reciprocating sliding wear test while low cycle and low applied normal load will caused low formation of cyclic plastic deformation.